2008
DOI: 10.1021/ja803109r
|View full text |Cite
|
Sign up to set email alerts
|

Gradient Shape-Persistent π-Conjugated Dendrimers for Light-Harvesting: Synthesis, Photophysical Properties, and Energy Funneling

Abstract: A new class of pi-conjugated dendrimers G0, G1, and G2 was developed through a double-stage divergent/convergent growth approach, in which 5,5,10,10,15,15-hexahexyltruxene was employed as the node and oligo(thienylethynylene)s (OTEs) with different lengths as the branching moieties. The dendrimers were fully characterized by (1)H and (13)C NMR, elemental analysis, gel permeation chromatography, and MALDI-TOF MS. Also, by using atomic force microscopy, it was observed that dendrimer G2 laid nearly flat on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
66
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(67 citation statements)
references
References 106 publications
1
66
0
Order By: Relevance
“…Among them, p-conjugated dendrimers belong to a class of macromolecules that have the advantage of highmolecular weights and defined and monodisperse chemical structures [13] and thus they have recently attracted much attention. Examples of 3D p-conjugated dendrimers include phenyl-ring-based systems such as polyphenylenes, [13,14] phenylenevinylenes, [15] phenyleneethynylenes, [16] and truxenes [17] or heterocyclic aromatic systems such as thiophenes, [18] carbazoles, [19] and phenothiazines. [20] In such conjugated denAbstract: Three-dimensional (3D) pconjugated dendritic oligothiophenes up to a third generation have been functionalized with tris-A C H T U N G T R E N N U N G (decyloxy)phenylethynyl tails at the periphery.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, p-conjugated dendrimers belong to a class of macromolecules that have the advantage of highmolecular weights and defined and monodisperse chemical structures [13] and thus they have recently attracted much attention. Examples of 3D p-conjugated dendrimers include phenyl-ring-based systems such as polyphenylenes, [13,14] phenylenevinylenes, [15] phenyleneethynylenes, [16] and truxenes [17] or heterocyclic aromatic systems such as thiophenes, [18] carbazoles, [19] and phenothiazines. [20] In such conjugated denAbstract: Three-dimensional (3D) pconjugated dendritic oligothiophenes up to a third generation have been functionalized with tris-A C H T U N G T R E N N U N G (decyloxy)phenylethynyl tails at the periphery.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of G0-2-1 and G0-4-2 (l max values of 360 nm and 465 nm, respectively) with the corresponding unsubstituted OTVs [21] revealed that the terminal truxene moiety participated in the conjugated system and thus induced a red shift in the l max value of 86 nm for G0-2-1 and 36 nm for G0-4-2. [23] Meanwhile, compared with G0 [13] and G1 [13] with oligothienylethynylene as the branch, dendrimers G0-2-1 and G0-4-2 exhibited a much broader absorption region, especially for G0-4-2, because of the better conjugation through the double bond than the triple bond. As mentioned earlier, such a broad and strong absorption spectrum is of great importance for organic solar cell materials with high energy-conversion efficiency.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Such small shifts implied that intermolecular aggregation (usually observed for OTV derivatives in thin films) was, to a large extent, suppressed by the truxene moieties with hexyl substituents and the overall dendritic structure. [13,28] The band gaps of dendrimers were estimated from the onset of absorption spectra in thin films. G0-2-1 has a band gap of 2.43 eV and G0-4-2 has a band gap of 2.00 eV; these values are slightly larger than that of PTV (E g = 1.74 eV).…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[41][42][43] The group of Pei developed a new class star-shaped dendrimers based on truxene that could be used as promising candidates for light-harvesting materials. [44][45][46] When twistacenes are implanted into the three-dimensional architectures, the as-formed novel dendrimers can effectively suppress intramolecular and intermolecular π-π stacking in high concentration solution and solid state without sacrificing other physical property. Nevertheless, current researches mainly focus on the synthesis and application of these derivatives in organic devices.…”
Section: Introductionmentioning
confidence: 99%